PENGGUNAAN LKPD BERBASIS HOTS UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI KELAS V SDN PABUARAN - Siti Irawati; Encep Andriana; Ratna Sari Dewi (Universitas Sultan Ageng Tirtayasa, 2021)
This research was motivated by observations in the field that the students' learning outcomes were not optimal, it could be seen from the pretest results of the fifth grade students which showed an average score of 65.71. Of the 21 students, there were 11 students who met the KKM with a learning completeness of 52.38% and 10 other students had not reached the KKM (70). This is caused by the difficulty of students understanding the material because it is not optimal in creating innovative learning that invites students to think critically. Online learning in general makes it difficult for teachers to guide students to solve HOTS-based problems, the practice questions given at school tend to test aspects of memory and understanding which do not train students to train HOTS. Therefore, researchers try to apply the use of HOTS-based worksheets which are expected to increase students' activities and learning outcomes. In this research is Classroom Action Research (CAR) which consists of three cycles. The subjects of this study were fifth grade students at SDN Pabuaran. From the results of learning improvements, the average value of the activity results of students in cycle I (2.09) is in sufficient category, cycle II (2.63) is in good category and cycle III (3.21) is in very good category. In addition to activities, student learning outcomes also increase as evidenced by improvements in aspects of attitudes, knowledge and skills. The average value of learning outcomes in the knowledge aspect using the evaluation sheet obtained in the first cycle (70.95) with 61.90% learning completeness, the second cycle (77.61) with 76.19% learning completeness and the third cycle (82.85 ) with learning mastery of 85.71%. Thus, the use of HOTS-based worksheets can improve student learning outcomes.